The Effect Of Sulphur (S) Doping and K+ Adsorption To The Electronic Properties Of Graphene: A Study By DFTB Method - Yuniawan Hidayat; Fitria Rahmawati; Eddy Heraldy; Khoirina Nugrahaningtyas; IF Nurcahyo (Jurnal Riset Kimia, 2022)
A study on the effect of S doping and K+ adsorption to the electronic properties of graphene has been conducted by DFTB (Density Functional Tight Binding) calculation. The supercell of 40 x 40 x 1 configured from the 4x4x1 unit cell of graphene was optimized. The calculation shows that the Fermi level of graphene shifted from -4.67 eV into -3.57 eV after S doping. In addition, the S presence caused the formation of gap within the Dirac K of valence band and conduction band. Meanwhile, K+ charge distribution was dominantly occurred within the S-graphene than the graphene.